ЛЕКАРСТВА И ПЕЧЕНЬ: неизменный тандем. Часть 1 - Е. Ю. Еремина (Архивъ внутренней медицины)
The article is devoted to the up-to-date data of the drug-induced liver diseases (DILD) problem and series of the clinical monitoring accomplished by the author. It contains the DILD risk factors, the main mechanisms and the clinical variants of the liver injuries and the main DILD diagnostics and treatment principles.